Incidência e impacto da função retardada do enxerto pancreático nos resultados dos transplantes simultâneos pâncreas-rim realizados na Universidade Federal de São Paulo - Baitello, Marina [UNIFESP] (2011)
Introduction: Simultaneous pancreas-kidney transplantation (SPKT) is an effective treatment for patients with type 1 diabetes and end-stage chronic kidney disease. Delayed pancreatic graft function (DGF) is a common and multifactor condition with significant impact in short-term outcome of SPKT. The aim of this study was to analyze the impact of pancreatic DGF on SPKT. Methods: Donor and recipient’s demographic data, percentage of panel reactivity, acute rejection incidence, and patient and grafts survivals were retrospectively analyzed in 180 SPKT performed between 2002 and 2007. Results: The incidence of pancreatic DGF was 11%. Donors older than 45 years had significant risk of pancreatic DGF (OR 2.26, p < 0,05). Patients with pancreatic DGF had higher rates of acute renal rejection (47% vs. 24%, p < 0.05), altered fasting plasma glucose (25% vs 5%, p < 0.05) and mean glycated hemoglobin (5.8% vs. 5.4%, p < 0.05), than patients without pancreatic DGF at the end of the first year of follow up. There were no significant differences between patients with and without pancreatic DGF regarding patient survival (95% vs. 88.7%, p = 0.38), pancreatic graft survival (90% vs. 85.6%, p = 0.59) and renal graft survival (90% vs. 87.2%, p = 0.70), respectively at the sample period of time. Conclusions: Pancreatic DGF had no significant impact in the short-term outcome of SPKT. Although pancreatic DGF had no impact on 1-yr pancreas graft survival, it contributed to early pancreas graft dysfunction, as assessed by enhanced insulin and oral anti-diabetic drugs requirements.